A Study on the Evaluation of Education Unions in Terms of Purposes and Activities Stated in their Constitutions - Engin DİLBAZ; Turan Akman ERKILIÇ (Anı Publishing, 2021)
This study aims to determine how education unions that have the most members in Turkey include the aims and activities in their statutes in terms of the functions of the unions. Furthermore, it aims to identify how the determined purposes and activities are distributed according to unions and the functions of the unions. The study is a qualitative research in the type of document analysis. Purpose and functions of the unions; their perspectives on politics and democracy, labour relations, education and development have been studies on the dimensions of socio-economic and socio-psychological functions. In the study, 27 evaluators selected from four groups as academicians, union managers, education administrators, and teachers were asked to classify items related to goals and activities in five categories. Based on the evaluators' classification, the Fleiss Kappa coefficient was found. At this stage, it was observed that the Fleiss Kappa value indicated a significant agreement. In the study, the constitutions of the four education unions with the highest number of members were examined in five dimensions. The data were analysed using the five-stage content analysis method. As a result, it is possible to suggest that education unionism in Turkey has an organisational mentality that emphasises social and political issues. It is concluded that it is necessary to conduct qualitative studies which aim to determine the purposes of unions, their determined goals, and which mission they have undertaken.